DAMPAK NEGATIF SENGKETA KEPULAUAN SENKAKU TERHADAP HUBUNGAN JEPANG DAN CHINA: STUDI KASUS 2010 - 2012 - JOHANTIKA, ALFARAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discusses about the effects of sovereignty dispute of Senkaku / Diaoyu Islands between Japan and China. This research tries to explain the negative effects about the relationship between Japan and China which appears in the case of sovereignty dispute of Senkaku / Diaoyu Islands. This research is divided into five chapters. The first chapter is an introduction that contains background of the research, problem formulation, purpose of the research, literature review, and writing systematic. The second chapter explains the geography location of Senkaku Islands and the factor of Senkaku Islands dispute. The third chapter explains the history of Senkaku Islands dispute. The forth chapter explains the effects of Senkaku Islands dispute and the last chapter is conclusion. This research concludes that there are four effects of Senkaku Islands dispute. They are, increasing the anti Japan in China, increasing fierce competition in the military field between Japan and China, worsening bilateral conditions between both countries and their economic conditions.